Swidden-fallow agroforestry in Amazonian: diversity at close distance - Jong, W. de (1996)
Swidden-fallow agroforestry among ribereño farmers in the Peruvian Amazon has been reported to show important regional variation. In this paper diversity in terra firme swidden-fallow agroforestry is described for a single village, Santa Rosa, located at the lower Ucayali river, Peru. Local forest gardens differ in managed species composition, weeding patterns, and yield levels. Most of the produce from Santa Rosa forest gardens is locally consumed; only little is traded. Many forest species are actively tended or planted in forest gardens. These systems have the function of suppliers of a range of products. Variation in forest garden management is a result of farmers individual perception of the need for such products.